Revised Procedure for Pavement Design under Seasonal Frost Conditions. - Berg,Richard L; Johnson,Thaddeus C (1983)
This report presents engineering guidance and design criteria for pavements at Army and Air Force facilities in seasonal frost areas. Design methods for controlling surface roughness and loss of subgrade strength during thawing petiods are provided. Criteria for using thermal insulating materials and membrane encapsulated soil layers in seasonal frost areas are presented. Six design examples are included. (Author)